Management of Multi Organ Dysfunction in Neonatal Encephalopathy - O'Dea, Mary; Sweetman, Deirdre; Bonifacio, Sonia Lomeli; El-Dib, Mohamed; Austin, Topun; Molloy, Eleanor J. (Frontiers in Pediatrics, 2020)
Neonatal Encephalopathy (NE) describes neonates with disturbed neurological function in the first days of life. NE is an overall term that does not specify the aetiology of the encephalopathy although it often involves hypoxia-ischaemia. In NE, although neurological dysfunction is part of the injury and is most predictive of long-term outcome, these infants also have multiorgan injury and compromise, which further contribute to neurological impairment and long-term morbidities. Therapeutic hypothermia (TH) is the standard of care for moderate to severe NE. Infants with NE have co-existing immune, respiratory, endocrine, renal, hepatic and cardiac dysfunction that require individualised management and can be impacted by TH. Non-neurological organ dysfunction not only has a negative effect on long term outcome but may also influence the efficacy of treatments in the acute phase. Post resuscitative care involves stabilisation and decisions regarding TH and management of multi-organ dysfunction. This management includes detailed neurological assessment, cardio-respiratory stabilisation, glycaemic and fluid control, sepsis evaluation and antibiotics, seizure identification and monitoring and responding to biochemical and coagulation derangements. The emergence of new biomarkers of specific organ injury may have predictive value and improve the definition of organ injury and prognosis. Further evidence-based research is needed to optimise management of NE, prevent further organ dysfunction and reduce neurodevelopmental impairment.